1968
DOI: 10.1530/jrf.0.0170419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vasopressin on the Uteroplacental Circulation: An Angiographic Study in the Rabbit

Abstract: The effect of vasopressin on the flow of blood through the uterus and placenta in the rabbit has been investigated by an angiographic technique, with contrast injection through a catheter inserted in the external iliac artery or selectively in the urogenital artery. It was found that the drug markedly reduced contrast filling of the vessels in the placentae and uterine wall including the placental sinuses. It is suggested that this effect was produced by constriction of the venules in the uterine vascular bed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

1970
1970
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
14
1
Order By: Relevance
“…Little is known about the response of the maternal placental circulation, however, although it is this component that is of decisive importance for the well-being of the fetus. We have already demonstrated that the pharmacodynamics of both the myo¬ metrial and the maternal placental circulations can be studied by angiography in the rabbit (Carter, Göthlin & Bengtsson, 1968;Carter & Göthlin, 1970). In the present investigation, the angiographie technique has been used to study the role of adrenoceptors in the control of myometrial and placental blood flow in the rabbit.…”
Section: Introductionmentioning
confidence: 82%
“…Little is known about the response of the maternal placental circulation, however, although it is this component that is of decisive importance for the well-being of the fetus. We have already demonstrated that the pharmacodynamics of both the myo¬ metrial and the maternal placental circulations can be studied by angiography in the rabbit (Carter, Göthlin & Bengtsson, 1968;Carter & Göthlin, 1970). In the present investigation, the angiographie technique has been used to study the role of adrenoceptors in the control of myometrial and placental blood flow in the rabbit.…”
Section: Introductionmentioning
confidence: 82%
“…The description of the origin of the uterine artery is also inconsistent among these prior studies (Krause, ; Tsuzaki, ; Bensley, ; Carter et al, ; Göthlin and Carter, ; Carter et al, ; Dickson et al, ; Janson and Svendsen, ; Orsi et al, ; Barone, ). Although Bensley (), Orsi et al (), and Barone () reported that the uterine artery arose from the umbilical artery, Carter et al (), Göthlin and Carter (), and Carter et al () reported that the uterine artery emerged from their “urogenital artery” (see the Discussion below), which originated from the common or internal iliac arteries and also gave rise to the cranial vesical artery. Other studies stated that the uterine artery originated directly from the common iliac artery (Krause, ; Tsuzaki, ), the internal iliac artery (Janson and Svendsen, ), or the common or internal iliac artery (Dickson et al, ).…”
mentioning
confidence: 95%
“…As to the branches of the uterine artery, Orsi et al () reported that the uterine artery gave rise to the vaginal, urethral, vesical, and rectal branches via various branching patterns. In other studies, however (Krause, ; Tsuzaki, ; Bensley, ; Carter et al, ; Göthlin and Carter, ; Carter et al, ; Dickson et al, ; Janson and Svendsen, ), the branches from the uterine artery were not described in detail.…”
mentioning
confidence: 95%
“…The uterine artery has been described previously on arteriography as a distended vessel coming off the internal iliac artery in pregnant does (Carter et al, 1968). However, this branch was not visible in this study where rabbits were not allowed to mate.…”
Section: Discussionmentioning
confidence: 48%